Strategy of Financing Management to Improve the Quality of Islamic Education Institution - Riinawati Riinawati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to reveal the strategy of improving the quality of Islamic educational institutions through financing management at MIN 1 Banjarmasin. This study used a qualitative approach with a natural setting as the data source. The data were collected through observation, in-depth interviews, and document review. There were five respondents in this study, namely the head of the madrasa, the head of the curriculum, the treasurer, the school committee, and the new student admissions committee. The results of the were the education financing management strategy in improving the quality of teachers, which emphasizes professionalism and discipline, as well as task commitment to improving school quality. Educational financing management strategies in an effort to foster students are carried out through coaching in the arts, by sports, religion, scouts, English, and personality. The education financing management strategy in the field of facilities and infrastructure is carried out by increasing funding sources, implementing quality improvement programs to support facilities and infrastructure as well as teacher welfare. The conclusion of this study is that the implementation of madrasa finance at MIN 1 Banjarmasin has been going well and its performance needs to be maintained and improved. Financing at MIN 1 Banjarmasin has been managed professionally. Based on the results of the analysis of the quality of education, there is a positive and significant relationship with financing management, where with financing management madrasas are able to plan things that support quality improvement, for example, reliable financing will support the provision of infrastructure that supports learning, teacher self-development, and academic and non- academic achievement. student academics.